2021
DOI: 10.3389/fphys.2021.659751
|View full text |Cite
|
Sign up to set email alerts
|

DsbA-L Ameliorates Renal Injury Through the AMPK/NLRP3 Inflammasome Signaling Pathway in Diabetic Nephropathy

Abstract: NLRP3-mediated inflammation is closely related to the pathological progression of diabetic nephropathy (DN). DsbA-L, an antioxidant enzyme, plays a protective role in a variety of diseases by inhibiting ER stress and regulating metabolism. However, the relationship of DsbA-L with inflammation, especially the NLRP3 inflammasome, has not been examined. In this study, we note that activation of the NLRP3 inflammasome and exacerbated fibrosis were observed in the kidneys of diabetic DsbA-L-knockout mice and were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…These processes may be associated with various infections and diseases that were inferred from the enrichment analysis of pathways, including influenza A, lipid dysfunction and atherosclerosis, and cancer. Previous studies have also shown that DN was associated with various autophagy-related biological functions ( Yang M. et al, 2021 ; Liu et al, 2022 ). Then, correlation analysis and the PPI network were constructed to further explore the correlation between the DEARG expression.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These processes may be associated with various infections and diseases that were inferred from the enrichment analysis of pathways, including influenza A, lipid dysfunction and atherosclerosis, and cancer. Previous studies have also shown that DN was associated with various autophagy-related biological functions ( Yang M. et al, 2021 ; Liu et al, 2022 ). Then, correlation analysis and the PPI network were constructed to further explore the correlation between the DEARG expression.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, novel and satisfactory strategies are urgently needed to treat DN. There is growing evidence that multiple biological functions are engaged in the pathogenesis of DN, such as immunity, inflammation, and autophagy ( Yang et al, 2019 ; Yang M. et al, 2021 ; Yu et al, 2021 ; Li et al, 2022 ). In our research, starting from autophagy, for the first time, we identified DEARGs in DN vs. normal human renal tubular interstitial cells by bioinformatics analysis, as well as determined a new autophagy-related biomarker for DN, thus providing novel insights into the tubulointerstitial pathogenesis of DN and contributing to the identification of novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation may play a crucial role in the pathophysiology of DN, as evidence is mounting [23][24][25]. Hyperglycemia can stimulate the secretion of inflammatory cytokines, induce apoptosis, and generate numerous reactive oxygen species, resulting in injury to renal tubular epithelial cells [26], renal [27], mesangial cells [28,29], and podocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AMPK signaling pathway was related to the renal inflammation ( Garcia and Shaw, 2017 ). Previous study by our group showed that DsbA-L could inhibit the activation of NLRP3 by activating AMPK phosphorylation in the kidney of DKD mice, while the expression levels of IL-18 and IL-1β were increased in that of DKD mice treated with compound C (an AMPK inhibitor) ( Yang et al, 2021a ). AMPK also inhibits the expression of inducible nitric oxide synthase (iNOS), thereby inhibiting the activation of NLRP3 inflammasome ( Pilon et al, 2004 ; Liao et al, 2021 ).…”
Section: Hyperglycemia-induced Inflammation In Dkdmentioning
confidence: 97%